Lean Manufacturing dengan PDCA untuk Peningkatan Kualitas Gula Semut Aren di PT. XYZ - Rexoprodjo, Monalisa; Abdul Rasyid; Monica Pratiwi (Jurnal Teknik, 2025)
Gorontalo has ±496,000 palm trees, yet 60% are unprocessed, and mostly used for alcohol. PT XYZ is here to shift farmers' focus to Aren Ant Sugar production. Its derivative products include Aren Ant Sugar, Batok, and Liquid. Batok Sugar is the result of reprocessing defective products from Ant Sugar which certainly requires additional time and costs. This research aims to identify the cause of the defect, which is a lumpy texture due to the pH of the nira water being below the standard (6-7). The Lean Manufacturing method with PDCA was applied as a solution, along with the innovation of using rambusa fruit net (Passiflora foetida) as an antibacterial and antioxidant. As a result, the DPU value dropped from 0.0845 to 0, proving an improvement in quality and production focus in Aren Ant Sugar.